The Role of the National and Political Unity Agency in Realizing Political Education for Beginner Voters Facing the 2024 Elections in West Sumbawa Regency - Suharno, Muhammad; Yamin, Ahmad; Suparman, Suparman (JUPE : Jurnal Pendidikan Mandala, 2023)
The National and Political Unity Agency in West Sumbawa Regency is regulated in West Sumbawa Regent Regulation Number 68 of 2019 concerning the Position, Organizational Structure, Duties and Functions and Work Procedures of the National and Political Unity Agency of West Sumbawa Regency.  Political Education organized by Bakesbangpol is a means of shaping leadership character in the younger generation.  When looking at the considerable potential of the younger generation, it is undeniable that political education is very important to be delivered early and known, understood by the people of Indonesia and the younger generation so that the people do not become political objects but also act as political subjects. Research Objectives 1) To describe the Role of the National and Political Unity Agency in the implementation of political education for novice voters facing the 2024 Concurrent Elections in West Sumbawa Regency, 2) to describe the Mechanism of the Political Education Program for the political awareness of novice voters facing the 2024 Concurrent Elections in West Sumbawa Regency.This study used descriptive research with a qualitative approach, data collection techniques through interviews, observation and documentation, with the Head of Kesbangpol as the key informant. The results of the study showed that the implementation of political education programs was carried out online and offline with material on nationalism and patriotism, national leadership, political leadership of the younger generation, national education policy. Thus, it can be concluded that the implementation of political education programs is carried out online and offline, the mechanism of political education programs by involving stakeholders. Suggestions required budgetary interventions from central, provincial and district governments for political education programs.